Relationship of obesity with the aggravation of COVID-19 (Research, Society and Development, 2022)
The objective of this study was to verify, through an integrative literature review, the relationship between obesity and the worsening of COVID-19. An integrative review was carried out. The search for articles was carried out in the PubMed, Scielo, Lilacs databases using the descriptors in Portuguese and English: “Obesidade”, “Agravação”, “COVID-19”, “Obesity”, “Aggravation” and “COVID-19”. 19", joined with the Boolean operator "AND". Access to the databases was carried out in the period of December 2021. 87 articles were found and after applying the inclusion criteria, 7 articles remained. are associated with an increased risk of diabetes, cardiovascular and kidney disease. WITH AGGRAVATING COVID-19, Being Linked to Deficiencies in Cardiovascular, Respiratory, Metabolic and Thrombotic Systems and Immune Responsibilities. In addition, a Presence of Other Chronic Noncommunicable Diseases (NCDs) can increase susceptibility to infections.